Selection of Kiwi Fruit Wine Specialized Yeast and Study on Fermentation Characteristics Based on Fuzzy Comprehensive Evaluation Method - Minghong BIAN; Qiang XU; Anqi ZHOU; Qin ZHANG; Hongbing LIAO; Shaolong LI; Baolin HAN (Shipin gongye ke-ji)
In order to improve the flavor and taste of kiwi fruit wine, this study took Xuxiang kiwi fruit and orchard soil as screening samples, combined with fuzzy comprehensive evaluation method to screen out the special strain suitable for the fermentation of Xuxiang kiwi fruit wine. The fermentation characteristics of yeast were studied. Initially, 13 yeast strains exhibiting favorable performance and acid-reducing capabilities were selected, from which 5 strains deemed suitable for kiwi fruit wine fermentation were identified through a fuzzy comprehensive evaluation method. Upon examination, JM-7, JM-72 and JM-76 were identified as Wickerhamomyces anomalus. JM-36 was Saccharomyces cerevisiae. JM-81 was Saccharomycopsis fibuligera. The highest DPPH free radical scavenging rate recorded was 76.16% in kiwi wine produced using JM-36, while the maximum ABTS+ free radicals scavenging rate and total reducing power were observed at 79.65% and 240.90 mg/L (calculated based on VC) in wine samples fermented with JM-72. The kiwi wine produced by JM-36 contained 30 distinct volatile components, with alcohol, acid, ester, and other substances comprising 30.10%, 23.05%, 42.14%, and 4.72% respectively. The concentrations of n-propanol, isobutanol, isoamyl alcohol, ethyl acetate, ethyl lactate, ethyl laurate, and ethyl caprylate were elevated. This composition contributes to a richer fruit and wine flavor in the kiwi wine. These yeasts could grow normally at temperatures of 24~32 ℃, pH of 3~4.5, sulfur dioxide concentrations of 0~100 mg/L, and alcohol concentrations of 0~6%, with JM-36 tolerating higher alcohol concentrations and lower pH. In conclusion, JM-36 could significantly enhance the flavor and aroma profiles of kiwifruit wine, and it is an excellent strain for the fermentation of kiwi fruit wine.